2018
DOI: 10.1021/acs.biochem.8b00195
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Side-Chain Dynamics in the Binding Site of Homeodomain/DNA Complexes As Observed by NMR Relaxation Experiments and Molecular Dynamics Simulations

Abstract: An important but poorly characterized contribution to the thermodynamics of protein-DNA interactions is the loss of entropy that occurs from restricting the conformational freedom of amino acid side chains. The effect of restricting the flexibility of several side chains at a protein-DNA interface may be comparable in many cases to the other factors that determine the binding thermodynamics and may, therefore, play a key role in dictating the binding affinity and/or specificity. Because the entropic contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 118 publications
(259 reference statements)
1
9
0
Order By: Relevance
“…We believe that other interesting aspects of protein disorder can be brought to light by a combination of NMR experiments and carefully designed MD studies. In particular, such a synergistic approach can be used to investigate the molten-globule state of proteins, the so-called ''fuzzy complexes'' (including complexes of disordered proteins with nucleic acids), electrostatic encounter complexes, models of folding intermediates, chemically denatured proteins, interdomain linkers, peptides with significant helical propensity (potentially experiencing helix-coil transitions), proline-rich peptides, and other highly variable systems (112)(113)(114)(115)(116)(117)(118)(119)(120).…”
Section: Resultsmentioning
confidence: 99%
“…We believe that other interesting aspects of protein disorder can be brought to light by a combination of NMR experiments and carefully designed MD studies. In particular, such a synergistic approach can be used to investigate the molten-globule state of proteins, the so-called ''fuzzy complexes'' (including complexes of disordered proteins with nucleic acids), electrostatic encounter complexes, models of folding intermediates, chemically denatured proteins, interdomain linkers, peptides with significant helical propensity (potentially experiencing helix-coil transitions), proline-rich peptides, and other highly variable systems (112)(113)(114)(115)(116)(117)(118)(119)(120).…”
Section: Resultsmentioning
confidence: 99%
“…Baired et al [95] made use of the NMR/MD combination to characterize protein-DNA interactions at hand of lysine side-chain 15 N-relaxation measurements and comparison to lysine dihedral angles obtained from a molecular dynamics trajectory. Thus, they could quantify the residual conformational freedom of charged lysine amines in TF-DNA complexes.…”
Section: Combining Nmr and MD Simulationsmentioning
confidence: 99%
“…Solution NMR studies of Arg and Lys side chains at the protein–DNA/RNA interfaces showed that basic side chains interacting with phosphate groups are generally more mobile than basic side chains interacting with nucleotide bases. 12 , 59 , 64 − 68 This difference in mobility may be related to steric restriction and other interactions in the grooves compared with those with the phosphate. More importantly, however, the dynamic equilibria between the CIP state and the solvent-separated ion pair (SIP) enhance the mobility of basic side chains forming ion pairs with phosphates ( Figure 4 A).…”
Section: Dynamics Of Macromolecular Ion Pairsmentioning
confidence: 99%